2022
DOI: 10.3390/bioengineering9070297
|View full text |Cite
|
Sign up to set email alerts
|

Microcarrier-Based Culture of Human Pluripotent Stem-Cell-Derived Retinal Pigmented Epithelium

Abstract: Dry age-related macular degeneration (AMD) is estimated to impact nearly 300 million individuals globally by 2040. While no treatment options are currently available, multiple clinical trials investigating retinal pigmented epithelial cells derived from human pluripotent stem cells (hPSC-RPE) as a cellular replacement therapeutic are currently underway. It has been estimated that a production capacity of >109 RPE cells annually would be required to treat the afflicted population, but current manufacturing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In addition to their role in cell delivery, scaffolds may also play a central role in enabling efficient large-scale production of stem cell-derived RPE for therapy. Faynus et al 101 reported the use of Cytodex microcarriers as scaffolds on which iPSC-RPE can be grown for harvest. The Cytodex (C) microcarriers are biologically inert, cross-linked dextran matrices that can be coated with Matrigel, vitronectin, or denatured type 1 porcine collagen to promote cell attachment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their role in cell delivery, scaffolds may also play a central role in enabling efficient large-scale production of stem cell-derived RPE for therapy. Faynus et al 101 reported the use of Cytodex microcarriers as scaffolds on which iPSC-RPE can be grown for harvest. The Cytodex (C) microcarriers are biologically inert, cross-linked dextran matrices that can be coated with Matrigel, vitronectin, or denatured type 1 porcine collagen to promote cell attachment.…”
Section: Introductionmentioning
confidence: 99%